(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Ascertaining an optimal cement distribution plan for cement companies in Nigeria has remained a challenge. The absence or fluctuation of data for estimating the cost of transporting cement from each source to each distribution center is a big stumbling block whenever modeling attempts are being made via transportation algorithms. This work has succeeded in removing these challenges by providing a Transportation Optimization Model for cement distribution using transportation Distance Matrix instead of transportation Cost Matrix. This research seeks to improve supply in the Nigerian cement industry. Three selected factories (Gboko, Port-Harcourt and Calabar) and four major distribution centers (Abakaliki, Onueke, Ohaozara and Afikpo) in Ebonyi state were considered for this work. The result of the findings using the Vogel Approximation Method, minimized the total transportation distance and by implication the total transportation costs.